Political Agroecology: Political Ecology critique of agrifood capitalism - Petersen, Paulo Frederico (Agrociencia Uruguay, 2022)
The emergence of Political Agroecology is presented as a derivation of Political Ecology applied to the analysis of power relations in agri-food systems regulation. At the same time that it elaborates a critique of the institutional foundations of the neoliberal agri-food regime, the Political Agroecology provides theoretical-conceptual and methodological references to support processes of institutional change so that agroecological practices can be used on growing social and geographic scales.